Interest in geological and palaeontological curiosities by southern African non-western societies: A review and perspectives for future study. Issue 5 (October 2019) - Helm, Charles W.; Benoit, Julien; Mayor, Adrienne; Cawthra, Hayley C.; Penn-Clarke, Cameron R.; Rust, Renee
Abstract: Compared with other parts of the world, the study of geomythology in southern Africa, and the associated documentation of non-western awareness of palaeontological and geological phenomena, is in an early phase. We focus on examples of rocks and fossils as items of special interest and curiosity, and we search for evidence of an indigenous palaeontology and geology. We review twenty-one sites or cases for which published accounts exist, and we describe a newly identified trilobite manuport site. In combination these sites provide various levels of evidence of palaeontological and geological awareness exhibited by non-western cultures in southern Africa, and how these cultures incorporated this knowledge into their understanding of their world. We anticipate that in time a diverse heritage of such 'natural knowledge' may become evident in southern Africa, aided in part by recognition of the possibility that rock art images may be associated with awareness of body fossils and trace fossils. We suggest ways in which further analysis may bolster this contention.